2019
DOI: 10.1101/760520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can scientists fill the science journalism void? Online public engagement with science stories authored by scientists

Abstract: 11

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…For communicators in the throes of a crisis, it is critical to convey factual, precise information that will also engage the general public. Under normal circumstances, communicating with technical, idiosyncratic words, or jargon, is viewed negatively by audiences [1][2][3][4][5][6][7][8][9]. In particular, research in science communication and beyond has found that the presence of jargon damages persuasive efforts [9] and can have a disengaging effect on audiences [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For communicators in the throes of a crisis, it is critical to convey factual, precise information that will also engage the general public. Under normal circumstances, communicating with technical, idiosyncratic words, or jargon, is viewed negatively by audiences [1][2][3][4][5][6][7][8][9]. In particular, research in science communication and beyond has found that the presence of jargon damages persuasive efforts [9] and can have a disengaging effect on audiences [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…A popular refrain in science communication is to avoid scientific language, otherwise known as jargon, when communicating with the general public [ 1 3 ]. Indeed, an abundance of research has revealed that the presence of jargon is alienating [ 4 ], undermines comprehension [ 5 ], reduces engagement [ 6 , 7 ], and creates a barrier to entry in certain fields (e.g., STEM) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%